ANALYSIS OF THE HEALTH LEVEL OF SHARIA PUBLIC FINANCING BANK (BPRS) BASED ON THE CIRCULAR LETTER OF THE FINANCIAL SERVICES AUTHORITY NUMBER 28 /SEOJK.03/2019 - Pandoyo, Pandoyo (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
Research aims: This study aims to analyze the health level of Sharia rural banks in Indonesia based on Financial Services Authority Circular Letter Number 28/SEOJK.03/2019. Design/Methodology/Approach: Secondary data were from Sharia Banking Statistics in May 2021 during 2009-2020. Research findings:  Based on the Circular Letter of the Financial Services Authority Number 28 /SEOJK.03/2019, it is known that Sharia rural banks have an adequate Capital Adequacy Ratio to absorb the risk of losses and write-off books due to decreased asset quality. So, the capital owned can absorb losses and fulfill the Minimum Capital Provision Obligation (KPMM) provisions in force. It has productive assets with a very high rate of return, so the proportion of problematic financing to total financing will be more measurable. It also has very high efficiency and stability, so it has the potential to obtain high profits. Theoretical contribution/ Originality:. Analysis of The Health Level of Sharia Public Financing Bank (BPRS) Practitioner/Policy implication: Financial Services Authority Number 28 /SEOJK.03/2019 Research limitation/Implication: BPR Sharia must still be able to answer various challenges because, in the future, BPR Sharia will face increasingly fierce competition levels, increasingly rapid technological developments, ecosystem changes, and digitalization, and also BPR Sharia must have strong capital